PaLean Manufacturing; A Sustainable Manufacturing Technique to help Indian Textile & Apparel Industry achieve Circular Economy and Aatmanirbharta. (Trinity Journal of Management, IT & Media (TJMITM), 2023)
This study aims to examine the potential of adopting circular economy principles  in the Indian Fashion and Textile industry and its feasibility through the adoption  of lean manufacturing practices, with the objective of achieving an “Atmanirbhar  Bharat” goal. The research utilizes a mixed-method approach, incorporating  discussions on the need of circularity and the potential way a head to achieve it  through Lean Manufacturing Technique and case discussion. The study investigates  the potential correlation between lean manufacturing, which emphasizes waste  reduction and operational efficiency in manufacturing processes, and the circular  economy concept,which revolves around minimizing waste, reducing resource  consumption,and promoting reuse and recycling. Circular economy strives to  establish a closed-loop system,instead of the existing Linear Economic System.  Through Lean Systems, the materials and products are utilized for as long as  possible, aiming to eliminate wastage. The Textile & Apparel industry ranks as the  second most polluting sector globally, contributing to environmental degradation,  social injustice, and economic instability.
Keywords: Atmanirbhar Bharat; Circular Economy; Indian Textile & Apparel Industry; Lean Manufacturing; Sustainability